Behavioral health correlates of exposure to community violence among African-American adolescents in Chicago. (October 2016) - Voisin, Dexter R.; Patel, Sadiq; Hong, Jun Sung; Takahashi, Lois; Gaylord-Harden, Noni
Abstract: Aims: Though public health researchers are more aware of behavioral health concerns among African American youth, few studies have explored how exposure to community violence may be related to adverse youth concerns. This study examines the relationship between exposure to community violence and mental health problems, substance use, school engagement, juvenile justice involvement, and STI risk behaviors. Methods: A total of 638 African American adolescents living in predominantly low-income, urban communities participated in the study by completing self-report measures on exposure to community violence, mental health, school engagement proxies, substance use, delinquency markers and sexual risk behaviors. Results: Adolescents who reported higher rates of exposure to community violence were significantly more likely to report poorer mental health, delinquent behaviors, a history of juvenile justice involvement, lower school bonding and student-teacher connectedness. These youth were also significantly more likely to use alcohol, cigarettes, and illicit substances, and engage in sexual risk behaviors. Conclusions: Findings suggest that there is a critical need for culturally relevant prevention and intervention efforts for African American adolescents who are frequently exposed to community violence. Highlights: Study examines the relationship between exposure to community violence (ECV) and behavioral health among poor black youth. Youth exposed to violence reported poorer mental health, delinquent behaviors, and juvenile justice involvement.. Youth who reported higher rates of ECV were more likely to report lower school bonding and student-teacher connectedness. Youth exposed to violence were more likely to use alcohol, cigarettes, drugs, and engage in risky sexual behaviors.